1969
DOI: 10.1177/00220345690480030501
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and Antigenic Studies of Lactobacilli Isolated from Deep Dentinal Caries: I. Biochemical Aspects

Abstract: Lactobacilli were isolated from 24 of 25 teeth with dentinal caries, using a nonselective medium. Biochemical studies indicated that all organisms were homofermenters, which reduced the pH below 4.5, grew at 15C (optimally between 30-37C), and produced predominantly the L(+) form of lactic acid. Eighteen organisms had identical carbohydrate utilization patterns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
1

Year Published

1973
1973
2005
2005

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 12 publications
1
4
0
1
Order By: Relevance
“…Thus, L. gasseri, L. rhamnosus, and a novel Lactobacillus phylotype (represented by clone L5) were the most numerically dominant species within the 65 carious dentine samples. With classic culture-based methods, L. casei, L. rhamnosus, and L. acidophilus are the most frequently isolated species (4,9,23,32,33).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, L. gasseri, L. rhamnosus, and a novel Lactobacillus phylotype (represented by clone L5) were the most numerically dominant species within the 65 carious dentine samples. With classic culture-based methods, L. casei, L. rhamnosus, and L. acidophilus are the most frequently isolated species (4,9,23,32,33).…”
Section: Discussionmentioning
confidence: 99%
“…Seventy-one percent of the carious fissures retained S. mutans, accounting for more than 10% of the viable count, whereas 70% of the fissures free from caries had no detectable levels of S. mutans (372). Furthermore, it has been shown that aciduric bacteria such as Lactobacillus are detected in significant quantities in the dentinal carious lesion as the decay progresses (373,525,561).…”
Section: Epidemiological Relationship Betweenmentioning
confidence: 99%
“…Another partial explanation for the absence of S. mutans could be the bacterial succession that occurs in the carious lesion. As the decay progresses into the dentine, the microenvironment appears to select for aciduric organisms such as Lactobacilli (26,37). In the dentinal lesion S. mutans is recovered from about half the samples (26; W. J. Armstrong, M.S.…”
mentioning
confidence: 99%